Immunology implantation - Pacheco Romero, José (2015)
In the process of reproduction, the fertilized egg is transported into the uterine cavity for implantation in the endometrium. We knew very little about how the process itself. Although the study is still not possible in humans, primates for research and in vitro observations now know that it is an episode of great magnitude and complexity, which leads to reflection of how difficult it is for a being implanted and survive to tell.